ICT resources and use: examining differences in pathways to improved small firm performance. Issue 7 (9th August 2021) - Beynon, Malcolm J.; Munday, Max; Roche, Neil
Abstract : Purpose: The paper shows how small firms perceive the pathways through which access to and adoption of superfast broadband-enabled resources strengthen business performance. Improvements to broadband infrastructure do not automatically lead to adoption of opportunities made available through the broadband resource. Then, interventions can be used to alert small firms to new opportunities. However, the quality of interventions in terms of education and digital audits can be better targeted with information available on how small firms perceive the benefits from broadband access and whether these perceptions are reflected in business performance outcomes. Design/methodology/approach: Data are used from the Digital Maturity Survey from Wales. The study uses principal component analysis and a dual stage cluster approach to show how SMEs believe they are benefitting from broadband access. These belief-based perceptions of broadband inferred business benefits are tested against business performance variables. Findings: The analysis shows variation in SME perceptions of the benefits of broadband-enabled services. This study reveals a cluster of firms which perceived routes to business value in terms of variables linked to security and risk management, and then more commonly held notions linked to communication, competition enhancement and productivity. Originality/value: While the research literature points to Information and Communication Technology (ICT) resources (ICT investment and skills) and use (digital applications), leading to new to business value improvements, this study suggests less work has sought to identify the critical themes identified by business owners in explaining how ICT resources and use tie to observed business performance. The study identifies these critical themes. The analysis suggests that these critical themes in terms of business value benefits as perceived by business owners can be summarised in terms of communication and competition benefits, and security and risk related benefits. The findings have a series of implications for interventions in the space.